Inside Back Cover: Programmable Polymer‐Based Supramolecular Temperature Sensor with a Memory Function (Angew. Chem. Int. Ed. 20/2014). Issue 20 (11th April 2014) - Sambe, Léna; de La Rosa, Victor R.; Belal, Khaled; Stoffelbach, François; Lyskawa, Joel; Delattre, François; Bria, Marc; Cooke, Graeme; Hoogenboom, Richard; Woisel, Patrice
Abstract : The heat was on! In their Communication on page 5044 ff., P. Woisel, R. Hoogenboom, G. Cooke et al. describe the supramolecular host–guest interactions between a poly( N ‐isopropylacrylamide) copolymer with naphthalene side chains and the tetracationic macrocycle cyclobis(paraquat‐ p ‐phenylene), which enabled the development of a (re)programmable thermometer that memorizes the thermal history of the solution and provides an associated visible readout.